Analysis of Potential Financial Distress Using the Altman Z-Score Method in the Property Sector Affected by High Interest Rates (Case Study: PT Lippo Karawaci Tbk Period 2023–2025) - Bella Putrie Nindyawan (Journal of Creative Power and Ambition (JCPA), 2026)
The tight monetary policy characterized by higher-for-longer interest rates during the 2023–2025 period poses a severe challenge to the capital-intensive property industry. This study aims to measure and analyze the potential of financial distress at PT Lippo Karawaci Tbk as an impact of these macroeconomic fluctuations. The research method employed is descriptive quantitative with a single case study design utilizing secondary data from audited financial statements for the 2023–2025 period. The corporate financial health was calculated using the Modified Altman Z-Score model through four variable components (X₁, X₂, X₃, X₄). The calculation results reveal that LPKR consistently remained in the Safe Zone, generating a Z-score of 2.985 in 2023, jumping to 4.976 in 2024, and reaching 5.423 in 2025, which comfortably exceeds the minimum critical threshold of Z > 2.90. Despite extreme contractive pressure on pure operating asset productivity driven by shrinking residential sales margins, corporate financial stability was salvaged by a drastic reinforcement in its capital structure and a radical reversal of retained earnings from deficit to surplus. This exponential financial leap was triggered by managerial strategic agility through the divestment of shares in its healthcare subsidiary, Siloam Hospitals, to settle its foreign currency-denominated senior notes. The research implications confirm that portfolio diversification and disciplined debt restructuring effectively act as a natural resilience in mitigating bankruptcy risks amidst external monetary crises